2007
DOI: 10.1007/s11192-007-0210-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the “value” of academic patents: IP management practices in UK universities and their implications for Third-Stream indicators

Abstract: Third-Stream activities have become increasingly important in the UK. However, valuing them in a meaningful way still poses a challenge to science and technology analysts and policy makers alike. This paper reviews the general literature on "patent value" and assesses the extent to which these established measures, including patent citation, patent family, renewal and litigation data, can be applied to the university context. Our study examines indicators of patent value for short and mid-term evaluation purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…For example, in the first group, the UK adopted a unique approach to technology transfer. Entrepreneurial activities in universities began to increase in the mid-1980s (Meyer and Tang, 2007), when heavy budget cuts forced universities to adopt more proactive approaches to revenue generation, which included the establishment of TTO. In the mid-1990s, government began actively supporting university "third mission" activities (Meyer and Tang, 2007).…”
Section: Regulations Policy Incentives Cultural Change and Their Immentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the first group, the UK adopted a unique approach to technology transfer. Entrepreneurial activities in universities began to increase in the mid-1980s (Meyer and Tang, 2007), when heavy budget cuts forced universities to adopt more proactive approaches to revenue generation, which included the establishment of TTO. In the mid-1990s, government began actively supporting university "third mission" activities (Meyer and Tang, 2007).…”
Section: Regulations Policy Incentives Cultural Change and Their Immentioning
confidence: 99%
“…Entrepreneurial activities in universities began to increase in the mid-1980s (Meyer and Tang, 2007), when heavy budget cuts forced universities to adopt more proactive approaches to revenue generation, which included the establishment of TTO. In the mid-1990s, government began actively supporting university "third mission" activities (Meyer and Tang, 2007). The main policy instrument was allocation of Higher Education Funding Council funds through calls for tender under various schemes for seed funding and entrepreneurial activity and the creation of official "third stream" funding for knowledge transfer activities, allocated on the basis of knowledge transfer performance measured by the annual Higher Education-Business and Community Interaction (HE-BCI) survey.…”
Section: Regulations Policy Incentives Cultural Change and Their Immentioning
confidence: 99%
“…At the moment there are three interpretations of the concept of universities' third mission (Molas-Gallart & Castro-Martínez 2007). One is associated with a 'third source of income' or a third stream of revenue related to knowledge transfer and licensing intellectual property rights (IPR) (e.g., Meyer & Tang, 2007) in collaboration with the private sector, private foundations, the European Union, etc. This is in contrast to universities' two traditional sources of income, namely, core appropriations direct from the public and funding from public research councils.…”
Section: Universities As An Actor In Society: the Third Missionmentioning
confidence: 99%
“…Studies have reported that assigned and litigated patents are more valuable than normal patents [18,19]. Therefore, these characteristics of patents were included in the model to verify their influence on patent maintenance time.…”
Section: Introductionmentioning
confidence: 99%